(untitled) (Quinto Sol, 2013)
In this paper we analyze the creation of new regulatory institutions, social practices and legal description of the crime in the State of Entre Ríos province, considering the context of the significant changes taking place in society Argentina during the second half of nineteenth century. As is known, in that period the first successful attempts to launch new institutional relationships and socio-economic gained momentum. From the Entre Ríos case study we analyze, first, the institutional changes of the province concerning land laws, tax structure and laws of discipline, as well as the powers of the control of political leaders and justice practices. Secondly, we explore changes in social practices, specifically within the environment of rural production and the labor market. Finally, we focus on the responses of actors to the new regulations.